Chemical Intercalant Affects the Structural Properties and Aqueous Stability of V2CTx MXene - Reagan A. Beers; Dijia Bao; Jessica R. Ray (Advanced Materials Interfaces)
Abstract Vanadium carbide (V2CTx) MXene is a 2D nanomaterial widely investigated for energy storage applications due to its superior electrochemical properties. However, V2CTx quickly degrades in water, which limits its performance and longevity. Furthermore, the relationship between V2CTx MXene synthesis parameters and their corresponding aqueous stability is underexplored. In this study, delaminated V2CTx MXene films synthesized with four tetraalkylammonium hydroxide intercalants were characterized for their structural and aqueous stability differences. Delaminated V2CTx MXene d‐spacing, flake edge lengths, and surface morphology were generally dependent on the intercalant radius. Specifically, the intercalant radius exhibited a positive correlation with d‐spacing and a negative correlation with flake edge lengths. These structural differences have direct impacts on the aqueous stability of V2CTx. For example, Raman spectra of each thin film indicated that amorphous carbon formation upon water exposure positively corresponded with flake edge lengths. 3D printed film holders were fashioned to mimic electrochemical cell configurations to evaluate vanadium dissolution from each film when exposed to water. Vanadium dissolution from each film was statistically similar (i.e., no correlation with intercalant radius) and substantial (i.e., ppm concentration range). These findings will benefit aqueous applications of V2CTx MXenes, where material degradation and vanadium release may impact MXene performance.